2004
DOI: 10.1109/tsm.2004.831925
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed AMHS and Its Operation Method for 300-mm QTAT Fab

Abstract: By using all-single-wafer processing in the 300-mm quick turn-around time production system, we have shortened cycle time to one-half or less than that of mixed-batch processing. We have also developed a high-speed automated material handling systems (AMHS) for achieving short cycle time. An intrabay rail-guided vehicle developed for the 300-mm fab is a component of this system. This paper describes the new system concepts, including AMHS hardware improvement, operation methods, and technician skill enhancemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…One previous research in 1994, by Lee et al proposed a system modeled by Petri Nets to integrate AGV models for material handling and models for part processing into a single coherent model to reduce labor cost in a flexible manufacturing system (FMS) (Lee et al 1994). In 2004, Wakabayashi et al developed a high speed automated material handling system to shorten cycle time by one half or less with new concepts, hardware improvements, and new operation methods in a wafer process for the 300-mm fab (Wakabayashi et al 2004). Later, Wu et al (2007) showed that a robot or an AGV can be both a material handling device and a buffer.…”
Section: Materials Handling Systemmentioning
confidence: 99%
“…One previous research in 1994, by Lee et al proposed a system modeled by Petri Nets to integrate AGV models for material handling and models for part processing into a single coherent model to reduce labor cost in a flexible manufacturing system (FMS) (Lee et al 1994). In 2004, Wakabayashi et al developed a high speed automated material handling system to shorten cycle time by one half or less with new concepts, hardware improvements, and new operation methods in a wafer process for the 300-mm fab (Wakabayashi et al 2004). Later, Wu et al (2007) showed that a robot or an AGV can be both a material handling device and a buffer.…”
Section: Materials Handling Systemmentioning
confidence: 99%
“…For normal lot cycle time, − smaller lot sizes and − single wafer processing tools only have been identified by a number of IC manufacturers as key architectural elements to improve normal lot cycle time (see [1], [7] or [9]). But how promising are these changes for priority lots?…”
Section: Improving Cycle Timementioning
confidence: 99%
“…The reality is that the market requires both higher performance devices using the latest process technology and shorter delivery time using the latest production technology Wakabayashi et al (2004). Most of the time, simulation of a real model, especially semiconductor manufacturing plant, is considered time consuming to construct due to a complex system configuration and requires long execution times to statistically produce valid estimate results Nazzal and McGinnis (2007).…”
Section: Introductionmentioning
confidence: 99%